TELAAH DIAKRONIK BAHASA BALI - I Kadek Widiantana; Ida Bagus Putrayasa (Masyarakat Linguistik Indonesia, 2023)
This study aims to describe the development of the Balinese language from the Old Balinese period to the present as a diachronic study of language. The source of the data is obtained through a literature study, namely looking for references that are considered relevant to the problem under study. The theoretical approach used is a historical linguistic approach through diachronic language studies and the methodological approach uses a qualitative descriptive approach. The results of this study show that Balinese vocabulary is influenced by various languages including Sanskrit, Old Javanese, Dutch, English, Portuguese, Chinese, and Arabic. Vocabulary from other languages is fully absorbed and some are experiencing changes from the original vocabulary. Absorption of vocabulary from other countries cannot be separated from interactions that occur with Balinese people, such as trade relations, colonialism, and the spread of religion.